The Relationship between Management Entrenchment and Audit Opinion Shopping - Afsaneh Lotfi (Iranian Journal of Accounting, Auditing & Finance)
The present study aims to assess the relationship between management entrenchment and audit opinion shopping in listed firms on the Tehran Stock Exchange. In other words, this paper attempts to figure out whether management entrenchment can contribute to audit opinion shopping or not. For this study, research hypotheses were tested using a sample of 768 observations on the Tehran Stock Exchange during 2012-2017 and by employing the Logistic Regression Pattern. The results show a significant relationship between management entrenchment and opinion shopping, which means entrenchment leads to increased opinion shopping. Management entrenchment is among managers' factors to increase authority, job security, interests, and corporate governance, contributing to the decline of management entrenchment. One of the mechanisms of corporate governance is the auditor’s opinion. There are few studies on the quality of corporate governance components in Iran, and this study can pave the way for further studies on the relationship of management entrenchment with other factors.